Upgrading the children. (Economist, 2009)
The article discusses the goal of the government of Rwanda to provide laptop computers to every child in the country between the ages of nine and 12. The desire of the Rwandan government to produce 50,000 computer programmers within the nation by the year 2020 is mentioned, noting that the charity One Laptop Per Child (OLPC) will supply the laptops to the children of Rwanda.